2016
DOI: 10.1063/1.4953593
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio modeling of zincblende AlN layer in Al-AlN-TiN multilayers

Abstract: An unusual growth mechanism of metastable zincblende AlN thin film by diffusion of nitrogen atoms into Al lattice is established. Using first-principles density functional theory, we studied the possibility of thermodynamic stability of AlN as a zincblende phase due to epitaxial strains and interface effect, which fails to explain the formation of zincblende AlN. We then compared the formation energetics of rocksalt and zincblende AlN in fcc Al through direct diffusion of nitrogen atoms to Al octahedral and te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As a target composition of InAsxP1x alloys, we focus on x=0.75 analogously to the previous experimental study of InAsP nanowires [16]. Orthorhombic supercells in a WZ and ZB phase are constructed with the primitive cell of each crystal phase by defining the lattice by (a,b,c)=(3a0,a0,c0) and (6a0,2a0,3a0) where a0,c0 are the cubic lattice constants for WZ and ZB, respectively [31]. The WB and ZB supercells consist of 16 and 48 atoms for WZ and ZB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a target composition of InAsxP1x alloys, we focus on x=0.75 analogously to the previous experimental study of InAsP nanowires [16]. Orthorhombic supercells in a WZ and ZB phase are constructed with the primitive cell of each crystal phase by defining the lattice by (a,b,c)=(3a0,a0,c0) and (6a0,2a0,3a0) where a0,c0 are the cubic lattice constants for WZ and ZB, respectively [31]. The WB and ZB supercells consist of 16 and 48 atoms for WZ and ZB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Three binary group-III-nitride crystalline structures (i.e. InN, AlN, and GaN) exist physically: wurtzite, zinc blende, and rock salt, as shown in figure 1 [9]. Wurtzite structures exhibit better thermodynamic stability at ambient temperature and pressure than the latter two lattice structures [1].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…found that the band bending at the ZB/WZ interface can lead to bound electron states within the enclosed WZ segment having sufficient length, as evidenced from the observed Coulomb blockade at low temperature by constructing homogeneous layered ZB/WZ/ZB SLs with precise control of WZ segment lengths. More interestingly, by controlling the mechanical property of a transformed WZ from ZB SLin AlN, the interfacial strain of the synthesized WZ or ZB phase structure can be tuned accordingly to suit the needs …”
Section: Introductionmentioning
confidence: 99%